Electrical properties of nanoscale field effect transistor. (2017) - Kausar, Sana; Joshi, Shirish
In this paper structure of a H-passivated silicon nanowire along [111] direction with hexagonal cross section is defined by using Virtual nanolab (VNL), and set up a nanoscale field effect transistor (FET) structure with a wrap-around gate. Then the transmission spectrum and conductance is computed as the gate bias is varied. The device characteristic curve and conductance with respect to gate voltage is studied. Also, the effect of doping of Al atom on characteristic curve and conductance of nanoscale field effect transistor is analysed.